(untitled) (Scientia Agricola, 2002)
The South American tomato pinworm, Tuta absoluta (Meyrick), is one of the most important tomato pests in Brazil and it has been controlled mainly by insecticides, which may be undesirable because of economical and environmental concerns. These problems can be minimized with alternative control tactics, such as the use of the resistant varieties. However, there is a lack of studies on alternative tactics to control T. absoluta. To obtain information on the insect-plant interactions, the number of instars of T. absoluta on two tomato genotypes: Lycopersicon hirsutum f. glabratum (PI 134417 - resistant) and L. esculentum (`Santa Clara' - susceptible) were determined. The experiment was carried out in climatic chambers, using two temperatures the 26 ± 0,5 and 30 ± 0,5ºC. Neonate larvae were fed with leaves of each genotype. Fifteen larvae of each treatment were removed daily to measure the width of the cephalic capsule. The development of the insect followed the Dyar's rule and four larval instars were found in all treatments.